Assessing the AQS/TAS-45 Indonesia Version for Children Attachment in Yogyakarta - Mutiah, Titik (Journal of Educational, Health and Community Psychology, 2012)
AbstractThe purpose of this study was to examine the Indonesia versions of the Attachment Q-Sort/AQS-Toddler Attachment Sort-45/TAS-45 (Bimler & Kirkland, 2002). Assessing the childs attachment in Indonesia has not been done lately. Data were collected through observation of 84 Indonesian toddlers residing in Yogyakarta. The validity of the TAS-45 was determined by Kirkland (2008) through mapping TAS-45 for the Indonesian users. This study had the inter-rater reliability of 0.92 that indicated the convincing score. The study finding shows the Indonesian AQS/TAS-45 is reliable and valid in for Indonesia children sample and suggest that the TAS-45 Indonesia version reflect similar concept to those in the original English versions.Keywords: AQS/TAS-45, Child, AttachmentÂ